RETRACTED: Digital tools in the study of social processes - Babaeva Anastasia; Makarova Alexandra; Shmeleva Natalya; Svadbina Tatyana; Nemova Olga (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001